Comparison of Gifted and Advanced Students on Motivation Toward Science Learning and Attitude Toward Science - Köksal, Mustafa Serdar (Journal of the American Academy of Special Education Professionals, 2013)
In this study, comparison of academically advanced science students and gifted students in terms of attitude toward science and motivation toward science learning is aimed. The survey method was used for the data collection by the help of two different instruments: "Attitude Toward Science" scale and "motivation toward science learning". Examination of reliability and validity of the scores on the instruments was conducted by using the "principle component analysis" with "varimax rotation" due to existence of a new group for validation of the instruments. The study involved 93 advanced science students and 12 gifted students who had higher IQ scores than 130 on WISC-R. The results of the study showed that the adapted instrument was valid and reliable to use for the measurements of motivation toward science learning in the context of advanced science classrooms. The comparisons of the groups in terms of the variables of the study showed that there is no statistically significant difference between the groups whereas there is significant difference between the groups in terms of the scores on the national examination.